Direktori Rental Mobil di Kota Padang Berbasis Website - Pratiwi, Aulya; Ardoni, Ardoni (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2018)
In this paper discuss about car rental directory in web based Padang city. This study aims to describe how the manufacture of car rental directory in Padang city based webmenggunakan PHP (Hyperlink Prepreccsor) based web aplication. This app is used as a tool to create car rental directory in web based Padang city. The method used is descriptive method with data collection technique through observation or direct observation to field, interview and literature study. From the observation and interviews conducted in the city of Padang then collected some data as a material to design a website that serves as a medium of information and promotion of car rental in the city of Padang. Based on the discussion of car rental information in the city of Padang, it can be concluded that the planning of this website is dynamic by using the application Framework codeIgnite (CI), which is a software designed specifically in the website design to install local website server as a liaison and support create a website using wamp server.Keyword: car rental directory web, Padang